PEMANFAATAN PLATFORM DIGITAL MARKETING SEBAGAI MEDIA PENJUALAN PRODUK PERTANIAN KELOMPOK TANI - ,, komariyati; Nugraha, A.; Kurniady, D. (Buletin Udayana Mengabdi; Vol 24 No 4 (2025): Buletin Udayana Mengabdi, 2025)
Technological developments require every business actor to be able to utilize information technology in marketing their products, as is the case with the Kamboja Farmers Group in Entikong District, Sanggau Regency, West Kalimantan. The marketing system that has been carried out so far is by using conventional marketing, namely direct buying and selling limited to friends, close friends, family, and middlemen. Along with the development of information technology, the Kamboja Farmers Group is trying to make a new breakthrough by making changes to the conventional marketing system by utilizing digital marketing to expand its market share. However, the challenge faced is that they have not mastered the use and application of digital marketing in selling their products. The purpose of this community service activity is to educate the use of digital marketing platforms as a medium for selling agricultural products sustainably at the Kamboja Farmers Group. The methods used are to conduct socialization, training, monitoring, and evaluation, as well as mentoring the use of digital marketing through Facebook social media. The output target in the form of increasing the knowledge of the administrators and members of the Kamboja Farmers Group regarding the role of utilizing digital marketing platforms (Facebook) has been achieved, as well as the existence of an online store on Facebook as a form of increasing skills in implementing digital marketing platforms as a medium for selling agricultural products.